SEMANTIC SYNTACTICAL FUNCTION OF COMPARATIVE CONJUNCTIONS IN MULTI RANGE PLANE - Донік, Ольга (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The article is devoted to the analysis for semantic syntactical sphere of comparative conjunctions in multi range plane. The urgency of paper expresses the insufficiency of theoretical developments in the sphere of abovementioned linguistic problem. The problem to distinguish the comparative expressions and subordinate parts in complex subordinated comparative sentences remains to be disputable. The purpose of proposed study is the complex research on functional stylistic potential for comparative conjunctions in multi range plane. The implementation of the purpose, being set, anticipates solving the following tasks: to clear up the essence of syncretism in linguistics; to describe the semantic syntactical kinds of comparative conjunctions; to describe the functional stylistic potential for comparative conjunctions in multi range plane. Results. It grounds the reasonability in distinguishing three kinds of comparative conjunctive means: conjunctions of similarity, identity and contrastive-comparative conjunctions. It clears up the laws of semantic syntactical function of conjunctions from different kinds in multi range plane. It clears up that all kinds of comparative conjunctions are used to establish the synthetic comparatives: conjunctions of similarity, which mark the likeness or propinquity of compared situations, conjunctions of identity, which express the absolute identity and contrastive-comparative conjunctions, which are not the exponents for complete or partial assimilation of situations and only with features of quantitative and qualitative preference, whether the one is compared over the other, with what or with whom is compared. Originality of the study is that it first analyzes the use of conjunctions in multi range plane. Conclusion. The problem, being raised, is urgent and emphasizes the perspective for further scientific searches in applied aspect. We also see the perspective for further scientific searches in study on specificity of stylistic function of comparative conjunctions.